Mini review: Apple improvement, traditional approaches, biotechnology options, and regulatory considerations - Klocko, Amy L. (Frontiers in Bioengineering and Biotechnology, 2025)
Apples are a popular and globally important crop. The fruits are eaten fresh, pressed for juice, fermented as cider, processed into sauce, dried, and more. There are thousands of different cultivars, a small subset of which are grown on a commercial scale. Genetic analysis has shown that, as a group, domestic apples have a complicated genetic background, with contributions from multiple wild species. By contrast, most of the highly produced commercialized modern cultivars share a narrow range of genetic diversity. However, as apples are outcrossing, propagated vegetatively, and long-lived, wild and heirloom varieties can be maintained and are valuable sources of genetic diversity for desirable traits. Apples are also amenable to genetic transformation, and work in this area has resulted in improved resistance to diseases and a commercialized non-browning variety, the Arctic™ Apple. Traditional breeding, breeding guided by modern genetic knowledge, and biotechnology all contribute to the overall process of apple cultivar development and represent an important example of how many approaches can be used in crop improvement. As global biosafety regulations continue to develop and change, countries will be tasked with developing guidelines for both the creation and import of apple trees and apple products.